Folylpolyglutamate synthetase mRNA G-quadruplexes regulate its cell protrusion localization and enhance a cancer cell invasive phenotype upon folate repletion - Michal Stark; May Levin; Igor Ulitsky; Yehuda G. Assaraf (BMC Biology, 2023)
Abstract Background Folates are crucial for the biosynthesis of nucleotides and amino acids, essential for cell proliferation and development. Folate deficiency induces DNA damage, developmental defects, and tumorigenicity. The obligatory enzyme folylpolyglutamate synthetase (FPGS) mediates intracellular folate retention via cytosolic and mitochondrial folate polyglutamylation. Our previous paper demonstrated the association of the cytosolic FPGS (cFPGS) with the cytoskeleton and various cell protrusion proteins. Based on these recent findings, the aim of the current study was to investigate the potential role of cFPGS at cell protrusions. Results Here we uncovered a central role for two G-quadruplex (GQ) motifs in the 3′UTR of FPGS mediating the localization of cFPGS mRNA and protein at cell protrusions. Using the MBSV6-loop reporter system and fluorescence microscopy, we demonstrate that following folate deprivation, cFPGS mRNA is retained in the endoplasmic reticulum, whereas upon 15 min of folate repletion, this mRNA is rapidly translocated to cell protrusions in a 3′UTR- and actin-dependent manner. The actin dependency of this folate-induced mRNA translocation is shown by treatment with Latrunculin B and inhibitors of the Ras homolog family member A (RhoA) pathway. Upon folate repletion, the FPGS 3′UTR GQs induce an amoeboid/mesenchymal hybrid cell phenotype during migration and invasion through a collagen gel matrix. Targeted disruption of the 3′UTR GQ motifs by introducing point mutations or masking them by antisense oligonucleotides abrogated cell protrusion targeting of cFPGS mRNA. Conclusions Collectively, the GQ motifs within the 3′UTR of FPGS regulate its transcript and protein localization at cell protrusions in response to a folate cue, inducing cancer cell invasive phenotype. These novel findings suggest that the 3′UTR GQ motifs of FPGS constitute an attractive druggable target aimed at inhibition of cancer invasion and metastasis.